Vortex pattern and differential conductance in hole underdoped high-temperature superconductors with competing d-wave and antiferromagnetic orders - Peng, Lin; Liu, Yongsheng (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Vortex charges in copper oxide high-temperature superconductors with hole underdoping are investigated by Bogoliubov–de Gennes equations based on a model Hamiltonian with competing antiferromagnetic order and d-wave superconducting order (DSC) with variation of temperature. For the DSC, spin density wave (SDW) and charge density wave (CDW), the transition from stripe to checkerboard pattern and to 2D structure may occur with variation of temperature. Moreover, both spatial profile of the electron density distribution and intensity of the differential conductance are strongly affected by the SDW order around the vortex cores. The transitions from one-dimensional to isotropic two-dimensional structures of the vortex charge and spin-density wave orders may occur by tuning the temperature.